Analisis Framing Berita Pembunuhan Balita di Apartemen Kalibata City Pada Media Massa Detik.com dan Kumparan.com - Nurhanami Rusirfah; Hendra Setiawan (Peneliti.net, 2023)
This research focuses on two news stories about the murder of a toddler in Kalibata City Apartment with two different mass media, namely Detik.com and Kumparan.com. Researchers analyzed the two news stories using the framing theory model of Zhongdang Pan and Gerald M. Kosicki. This theory has four structures, namely syntactic, thematic, script, and rhetorical. This research uses a qualitative approach with a descriptive method. The results of the analysis found are that both media have the same sources. In addition, another result is that the media Detik.com more coherent and detailed in providing information about the murder event. Meanwhile, the Kumparan.com media not only provided information on the murder incident that occurred, but also highlighted the news about the murder suspect.